2018
DOI: 10.1007/s10584-018-2321-0
|View full text |Cite|
|
Sign up to set email alerts
|

Does climate-smart village approach influence gender equality in farming households? A case of two contrasting ecologies in India

Abstract: Evidence from climate-smart village (CSV) approach to mainstream climate-smart agriculture (CSA) demonstrates improved productivity, income, and reduced climatic risks. However, its contribution to gender empowerment in diverse farming households is not documented. This study creates a Gender Empowerment Index for climate-smart villages (GEI-CSV) based on four major measurable indicators-political, economic, agricultural, and social. The gender gap was derived by mapping difference in empowerment levels across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Projects may define empowerment loosely as 'better participation in the decision-making process' 57 , with a focus on equal opportunity. Equating equal numbers with empowerment can lead to a 'tyranny of participation' 44 , whereby turning up is defined as empowerment, and the social, cultural and structural barriers to meaningful empowerment are neither acknowledged or addressed 58 Simply encouraging equal numbers of women to participate may merely serve to reinforce traditional gender roles.…”
Section: Gender Equality Is a Numbers Gamementioning
confidence: 99%
“…Projects may define empowerment loosely as 'better participation in the decision-making process' 57 , with a focus on equal opportunity. Equating equal numbers with empowerment can lead to a 'tyranny of participation' 44 , whereby turning up is defined as empowerment, and the social, cultural and structural barriers to meaningful empowerment are neither acknowledged or addressed 58 Simply encouraging equal numbers of women to participate may merely serve to reinforce traditional gender roles.…”
Section: Gender Equality Is a Numbers Gamementioning
confidence: 99%
“…In addition, a number of impact assessments have also been conducted, to evaluate impact of the program's efforts to end users (Gill, 2014;Aryal et al, 2015;Murendo and Wollni, 2015;Reddy, 2015;Hariharan et al, 2020). The program's accountability to facilitating outcomes also received favorable review in the program-wide evaluation, wherein accountability within the CCAFS program was considered to be enhanced as a result of the results based management and the associated approach of developing theories of change (Anderson et al, 2016).…”
Section: Accountabilitymentioning
confidence: 99%
“…Differences among regions, villages, or among landscapes can also account for differences in adaptation, vulnerability, or empowerment levels among women. For example, in a study in two Indian CSVs, Hariharan et al [37] found that overall women in the Bihar CSV had a lower degree of empowerment than women in the Haryana CSV when measured using the "Gender Empowerment Index", which assesses men's and women's progress in both the use of sustainable farming practices and economic returns from agricultural enterprises as well as improvements in social and political engagement. The authors attributed that fact to the broadly lower level of empowerment among both men and women in Bihar.…”
Section: Introductionmentioning
confidence: 99%